Penggunaan Metode Extreme Programming Pada Perancangan Sistem Informasi Pelayanan Publik - Noer Azni Septiani; Faauzan Yusuf Habibie (Universitas Budi Darma, 2022)
Sodong Tigaraksa Village with the Golden Village idea is in dire need of applications that support and provide satisfactory public services for its citizens, applications to help gather data, manage data and provide information easily and quickly. citizen data collection, to storing other data, to making reports, making it possible during the process there were errors in recording, inaccurate reports made and delays in finding the required data. For this reason, this study aims to create a web-based application using the Extreme Programming (XP) method which is useful for Sodong Village to facilitate data processing in public services and a database design tool in the form of ERD (Entity Relationship Diagram). In software development there are several approaches or methods used, the programming language used is PHP and the database used in the construction of the system is MySQL in this study the method used is Extreme Programming (XP) to build a public service information system, the design of this information system using the extreme programming (XP) method is the best solution to solve the problems that exist in this Sodong Village public service.